Factors influencing modern contraceptive usage among women aged 15-49 years: a cross-sectional study - Mohammed-Amen, Hawri Yaba; Ali, Suhailah Mohammed (Jurnal Ners, 2024)
Introduction: This study aimed to examine the factors that influence modern contraceptive use among married women of reproductive age in Kirkuk City, Iraq. Methods: A cross-sectional study was conducted to gather data from a convenience sample of 500 married women of reproductive age attending family planning units at 10 healthcare facilities, Azadi, Kirkuk Teaching Hospital, and private gynecological and obstetric clinics. Data were collected using a structured questionnaire from October 1st, 2023, to February 1st, 2024. The statistical analysis involved descriptive and inferential techniques. Results: The prevalence of contraceptive use among participants was 74.6%, with about (21%)  reporting condom use and (16.0%) withdrawal usage. However, intrauterine devices were reported in (12.6%). Side effects were significantly (p<0.001) associated with contraceptive method choices, with 52% of the users experiencing adverse effects. External pressures to have additional children or become pregnant significantly (p=0.037) influenced contraceptive method choices. There were fewer modern contraceptive methods due to unsafety (30.9%), discomfort (23.6%), and side effects, such as headache (18%), weight gain (16%), and irregular bleeding (14%). Conclusions: Modern contraceptive use is affected by healthcare, safety, side effects, reproductive health, and personal choices. Providing complete knowledge and access to modern contraceptives helps couples make informed reproductive health decisions, empowers women to regulate their fertility, supports their personal and reproductive objectives, and promotes their health and well-being. Keywords: birth control, childbearing age, Iraq, modern contraceptive, side effects